A Study On Job Satisfaction With Reference To Lanco Kondapalli Power Ltd Ap, India. (International Journal of Scientific Research and Management (IJSRM), 2016)
Human resources are coal-and ice to every organization. As we know customer is king to the market parallel an employee is god to the every business concern because he/she has to gifted their services to the concern until unless the concern will not be resulted as profitable concern. Our Indian market is a threshold to employment opportunities, attaining a job is a child’s play but, in recent days how many people are gratified is a hundred million dollars question to all. This study is going to give you clarity regarding satisfaction of an employee at work place, every employee got paid by the employer promptly even we can’t consider that as he/she satisfied in their job. To breakout this we associated with LANCO KONDAPALLI POWER LTD AP INDIA, Satisfying an employee is not a simple task as thought as we can , an employer also has to show some interest towards employees satisfaction i.e., accommodate healthy working environment may advised over here, because that is also one of the significant point to the employees. So, we made an analysis on job satisfaction in LANCO Kondapalli Power LTD AP INDIA, in this analysis we have discovered inexperienced circumstances at working place